Bio-nanocapsules for oriented immobilization of DNA aptamers on aptasensors. Issue 3 (13th January 2022) - Iijima, Masumi; Yamada, Yuki; Nakano, Hideo; Nakayama, Tsutomu; Kuroda, Shun'ichi
Abstract : The oriented immobilization of sensing molecules ( e.g., IgGs, receptors, lectins, and DNA aptamers) on sensor chips is particularly important for maximizing the sensitivity and target-binding capacity of biosensors. Abstract : The oriented immobilization of sensing molecules ( e.g., IgGs, receptors, lectins, and DNA aptamers) on sensor chips is particularly important for maximizing the potential of the sensing molecules, thereby enhancing the sensitivity and target-binding capacity of biosensors. We previously developed ∼30 nm bio-nanocapsules (ZZ-BNCs) consisting of the hepatitis B virus envelope L protein fused with the tandem form of protein A-derived IgG Fc-binding Z domain (ZZ-L protein). ZZ-BNC acts successfully as a scaffold, enhancing both the sensitivity and binding capacity of IgG, a Fc-fused receptor, and Fc-fused lectin to antigens, cytokines, and sugar chains through an oriented immobilization on a biosensor surface. To expand the versatility of ZZ-BNC, we modified ZZ-BNC by replacing the ZZ domain with a DNA-binding single-chain lambda Cro (scCro) domain, thereby developing scCro-BNC. The scCro-BNC was synthesized in yeast cells and homogeneously purified as ∼30 nm sized nanoparticles. In a quartz crystal microbalance, an scCro-BNC-coated sensor chip immobilized with thrombin-binding DNA aptamers showed an ∼5.5-fold higher thrombin-binding capacity and ∼6000-fold higher detection sensitivity than a sensor chip directly coated with DNA aptamers. In addition, the number of bound thrombin molecules per molecule of DNA aptamer increased by ∼7.8-fold with an scCro-BNC coating, consistent with the theoretical thrombin-binding capacity. Collectively, scCro-BNC was shown to perform as an ideal scaffold for maximizing the potential of the DNA aptamer by immobilizing it in an oriented manner. Facilitating a highly sensitive detection of various target molecules, these BNC-based scaffolds are expected to improve a wide range of biosensors while minimizing the number of sensing molecules required.